Redução da carga horária para pais de crianças com transtorno do espectro autista: as lacunas jurídicas e as dificuldades enfrentadas no mercado de trabalho - (:unkn) unknown (Universidade Federal do Pampa, 2024)
Autism Spectrum Disorder (ASD) is a disorder characterized by alterations in neurodevelopmental functions. Children with ASD therefore require a set of specific practices that can help promote their well-being and social inclusion. In this sense, on the one hand, there are several legal guarantees for infants with Autism Spectrum Disorder, but, on the other, there are not sufficient rights to ensure full monitoring and dedication of necessary care by the parents. parents of these children, who work under the CLT regime and need to reconcile different demands. It is precisely this thematic delimitation that this Course Completion Work focuses on. Therefore, the guiding problem of the study lies in the following question: are there legal provisions that regulate the need to reduce CLT working hours for parents of children with Autism Spectrum Disorder? In fact, the rigidity of the standard eight-hour working day can be an obstacle to adequate support for the development of autistic children. However, the embryonic hypothesis points to a normative gap that guarantees this right to workers under such conditions and governed by the Consolidation of Labor Laws (CLT). This requires jurisprudential understanding and extensive interpretation of laws that are not specific to the aforementioned target audience. In general, the aim is to contribute to the promotion of equality and prevention of discrimination against autistic children and their families. Bringing visibility to identify legal gaps and impacts on human rights. Specifically, in each of the chapters of the work development, the objective is: i. conceptualize Autism Spectrum Disorder and the needs of children with this diagnosis; ii. analyze national and international regulations regarding autism; iii. investigate the demand for care for children with ASD and the reconciliation of parents with their working hours, verifying the need for a national law that regulates the reduction in CLT working hours. In pursuing this monographic work, of an exploratory type, of a basic nature and with a qualitative approach, the hypothetical-deductive scientific method was used to test the hypothesis emerging from the problem raised and, thus, develop systematic theoretical knowledge about the proposed theme through the use of indirect bibliographic and documentary research technique. Finally, it is stated that the work does, in fact, have legal relevance in several aspects, especially due to the lack of specific laws that regulate the problematized issue.
Keywords: Horário de trabalho; Pais de crianças autistas; Direito do trabalho; Direitos Humanos; Brasil - [Consolidação das leis do trabalho (1943)]; Transtorno do espectro autista; Horário de trabalho flexível; Working hours; Parents of autistic children; CNPQ::CIENCIAS SOCIAIS APLICADAS